EVALUATION OF GROWTH AND SURVIVAL OF OREOCROMIS NILOTICUS IN A BIOFLOC SYSTEM - RAFIQUE , HM; ALYAS , S; AHMAD , S; AMBREEN, S; GUL , A (Biological and Clinical Sciences Research Journal, 2024)
The global demand for Nile tilapia (Oreochromis niloticus) is rapidly increasing. To meet this demand, a green technology known as fast biofloc was introduced, although its intensive application on an industrial scale remains limited. Objective: This study aimed to evaluate the effects of advanced biofloc technology (BFT) on water quality parameters, growth, and survival of Nile tilapia to optimize water quality and maximize overall tilapia growth. Methods: A 90-day experimental study was conducted from May to July 2021 at the Fish Biodiversity Hatchery Chashma, district Mianwali, Punjab, Pakistan. The experiment utilized a controlled and a bio floc treatment, each managed in 10,000 L outdoor tanks. A total of 1,670 Nile tilapia, with an average weight of 3.2 g and length of 2.2 cm, were stocked in each tank. The BFT and control tanks were fed a diet containing 30% crude protein (CP) at 20% of the total fish biomass daily. Additionally, the BFT tank received probiotics, molasses, and salt. Critical parameters such as water quality, floc volume (FV), growth rate, and feed conversion ratio (FCR) were measured. Statistical analyses were conducted at a significance level of p ≤ 0.05. Results: The nutritional quality of biofloc was suitable for tilapia, and no significant differences were observed in water quality parameters between the BFT and control tanks. Floc volume was only present in the BFT tank, measuring 28 g. The BFT treatment resulted in significantly higher growth rates and performance than the control (p ≤ 0.05), with net fish production being 72% higher in the BFT tank. The average FCR was 2.2 in the BFT tank and 3.1 in the control tank, indicating more efficient feed utilization in the BFT system. Conclusion: Compared to the control, the bio floc system enhanced the Nile tilapia’s water quality, growth performance, and survival rates. These findings suggest that biofloc technology is a viable and effective method for sustainable aquaculture, offering substantial benefits regarding fish growth and resource efficiency.